Is Excess PbI2 Beneficial for Perovskite Solar Cell Performance?. Issue 7 (13th January 2016) - Liu, Fangzhou; Dong, Qi; Wong, Man Kwong; Djurišić, Aleksandra B.; Ng, Annie; Ren, Zhiwei; Shen, Qian; Surya, Charles; Chan, Wai Kin; Wang, Jian; Ng, Alan Man Ching; Liao, Changzhong; et al.
Abstract : Unreacted lead iodide is commonly believed to be beneficial to the efficiency of methylammonium lead iodide perovskite based solar cells, since it has been proposed to passivate the defects in perovskite grain boundaries. However, it is shown here that the presence of unreacted PbI2 results in an intrinsic instability of the film under illumination, leading to the film degradation under inert atmosphere and faster degradation upon exposure to illumination and humidity. The perovskite films without lead iodide have improved stability, but lower efficiency due to inferior film morphology (smaller grain size, the presence of pinholes). Optimization of the deposition process resulted in PbI2 ‐free perovskite films giving comparable efficiency to those with excess PbI2 (14.2 ± 1.3% compared to 15.1 ± 0.9%) Thus, optimization of the deposition process for PbI2 ‐free films leads to dense, pinhole‐free, large grain size perovskite films which result in cells with high efficiency without detrimental effects on the film photostability caused by excess PbI2 . However, it should be noted that for encapsulated devices illuminated through the substrate (fluorine‐doped tin oxide glass, TiO2 film), film photostability is not a key factor in the device degradation. Abstract : PbI2 residue‐containing perovskite films are intrinsically unstable under illumination. While the excess PbI2 improves the cell efficiency due to improved perovskite layer morphology, optimization of the deposition leads to lead iodide‐free films with improved photostability and high efficiency. However, compared to photodegradation, other processes are more important in device degradation.